Assessment of behavioral changes associated with oral meloxicam administration at time of dehorning in calves using a remote triangulation device and accelerometers - Theurer, Miles E.; White, Bradley J.; Coetzee, Johann F.; Edwards, Lily N.; Mosher, Ruby A.; Cull, Charley A. (My University, 2013)
Background: Dehorning is common in the cattle industry, and there is a need for research evaluating pain mitigation techniques. The objective of this study was to determine the effects of oral meloxicam, a non-steroidal anti-inflammatory, on cattle behavior post-dehorning by monitoring the percent of time spent standing, walking, and lying in specific locations within the pen using accelerometers and a remote triangulation device. Twelve calves approximately ten weeks of age were randomized into 2 treatment groups (meloxicam or control) in a complete block design by body weight. Six calves were orally administered 0.5 mg/kg meloxicam at the time of dehorning and six calves served as negative controls. All calves were dehorned using thermocautery and behavior of each calf was continuously monitored for 7 days after dehorning using accelerometers and a remote triangulation device. Accelerometers monitored lying behavior and the remote triangulation device was used to monitor each calf’s movement within the pen. Results: Analysis of behavioral data revealed significant interactions between treatment (meloxicam vs. control) and the number of days post dehorning. Calves that received meloxicam spent more time at the grain bunk on trial days 2 and 6 post-dehorning; spent more time lying down on days 1, 2, 3, and 4; and less time at the hay feeder on days 0 and 1 compared to the control group. Meloxicam calves tended to walk more at the beginning and end of the trial compared to the control group. By day 5, the meloxicam and control group exhibited similar behaviors. Conclusions: The noted behavioral changes provide evidence of differences associated with meloxicam administration. More studies need to be performed to evaluate the relationship of behavior monitoring and post-operative pain. To our knowledge this is the first published report demonstrating behavioral changes following dehorning using a remote triangulation device in conjunction with accelerometers.
Keywords: Oral meloxicam; Behavior; Dehorn; Dehorning; Remote triangulation device